1988
DOI: 10.1136/ard.47.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate ototoxicity in patients with rheumatoid arthritis: a controlled study.

Abstract: SUMMARY Tinnitus or subjective hearing loss, or both, were reported by 61 of 134 (45%) patients with rheumatoid arthritis (RA) taking regular salicylates and by 73 of 182 (40%) untreated healthy subjects. In the patients with RA mean salicylate levels were not higher in those with tinnitus than in those without tinnitus, but levels were significantly higher in those with subjective hearing loss than in those with no symptoms. Twenty five per cent of the patients with RA had tinnitus or subjective hearing loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 6 publications
(3 reference statements)
0
31
0
2
Order By: Relevance
“…Mongan et al (1965) (Myers et al, 1973). More recently, Halla & Hardin (1988) reported that tinnitus and deafness could occur below these threshold levels.…”
Section: Introductionmentioning
confidence: 99%
“…Mongan et al (1965) (Myers et al, 1973). More recently, Halla & Hardin (1988) reported that tinnitus and deafness could occur below these threshold levels.…”
Section: Introductionmentioning
confidence: 99%
“…Salicylate, a widely used anti-inflammatory drug, has been shown to induce tinnitus [5,6,7,8,36,37,38]. In this work, we performed experiments with salicylate at a concentration of 350 mg/kg based on the literature [4,39,40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The two waves are thought to interact and create a sound wave that is of the frequency 2f1 À f2, which travels toward the input direction (Dalhoff et al 2007). The resultant wave travels through the cochlea, out of the oval window, and through the middle ear where it is emitted from the tympanic membrane as a noise (Hall 2000). The noise can be averaged and the intensity defined for pretest and postdose evaluations.…”
Section: Distortion Product Otoacoustic Emissionsmentioning
confidence: 99%